Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1097/00140068-200301001-00021
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme and Lipid Deposition on Silicone Hydrogel Contact Lens Materials

Abstract: The quantity and conformation of lysozyme and the quantity of lipid deposited on hydrogel contact lenses is significantly influenced by the composition of the lens material. SH contact lens materials deposit low levels of lysozyme and high levels of lipid deposition compared with ionic contact lens materials. Although SH materials deposit only small amounts of lysozyme, the degree of lysozyme denaturation that occurs is higher relative to that seen on ionic lens materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
186
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(204 citation statements)
references
References 12 publications
9
186
6
Order By: Relevance
“…The high water content and the ionic material of some disposable soft lenses allow for more deposition of proteins, a fact that could explain the greater affinity of the Acanthamoeba protozoon for worn lenses than for unworn ones. 39 Jones et al 44 reported significant deposition of low levels of lysozyme and high levels of lipid on silicone hydrogel contact lens materials, as compared with ionic contact lens materials. The adhesion of Acanthamoeba in unwashed worn versus unwashed unworn contact lenses showed a significantly lower adherence of Acanthamoeba to new lenses.…”
Section: Duration Of Exposure and Protozoon Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The high water content and the ionic material of some disposable soft lenses allow for more deposition of proteins, a fact that could explain the greater affinity of the Acanthamoeba protozoon for worn lenses than for unworn ones. 39 Jones et al 44 reported significant deposition of low levels of lysozyme and high levels of lipid on silicone hydrogel contact lens materials, as compared with ionic contact lens materials. The adhesion of Acanthamoeba in unwashed worn versus unwashed unworn contact lenses showed a significantly lower adherence of Acanthamoeba to new lenses.…”
Section: Duration Of Exposure and Protozoon Concentrationmentioning
confidence: 99%
“…111 Old contact lenses could colonise more microorganisms due to the increased lens surface tear and wearrelated scratches 40 or to the accumulated deposits. [43][44][45] The relationship between repeated use of daily disposable lenses and risk of Acanthamoeba 112,113 and microbial keratitis 93,114 is well established.…”
Section: Non-compliant Contact Lens Usersmentioning
confidence: 99%
“…44 There were no differences in the TSQ after seven days of lens wear compared with the first day of wear, neither for the hydrogel nor for the silicone hydrogel lenses. This was in spite of the fact that group-4 hydrogels (high water content ionic materials) are known to significantly accumulate lysozyme deposits [45][46][47][48] and silicone hydrogel lenses are prone to lipid accumulation [48][49][50][51] over contact lens wearing time. One of the more interesting findings of this study was a slight, but statistically significant improvement in TSQ during the first day of silicone hydrogel lens wear.…”
Section: Discussionmentioning
confidence: 99%
“…Research on conventional poly-HEMA-based lens materials has shown that the deposition of lysozyme and albumin depends upon the polymer's composition (Bohnert et al, 1988), charge (Garrett et al, 2000;Soltys-Robitaille et al, 2001) and water content (Garrett et al, 1999). Silicone-hydrogel materials give rise to different deposition profiles to those associated with the use of conventional poly-HEMA hydrogel lenses in that they induce less protein deposition and more lipid deposition (Jones et al, 2003;Subbaraman et al, 2006;Carney et al, 2008). Surface roughness also need to be considered since deposits are more likely to form on imperfections of the lens surface (Hosaka et al, 1983).…”
Section: Introductionmentioning
confidence: 99%